Figurative Language Analysis of the Poetry “I Want” by Sapardi Djoko Damono - Yuni Ratna Purwaningsih (Departement of Mathematics Education, 2023)
The aim of this research was to analyze the poetry by Sapardi Djoko Damono on the title “I Want” with a figurative language method. The type of this research was descriptive qualitative and took the data by note of the poetry. The data was collected and analyzed by taking several phrases of the poetry. The results of the figurative language analysis of the poem